EFFECTS OF TAMSULOSIN 0.2 MILIGRAM AND TAMSULOSIN 0.4 MILIGRAM ON LOWER URINARY TRACT SYMPTOM SCORE OF USSQ IN PATIENTS WITH INDWELLING DJ STENTS - Rizki, Dhika Ari; Safriadi, Ferry; Noegroho, Bambang S (Indonesian Journal of Urology, 2020)
Objective: To assess the difference in the administration of 0.2 mg and 0.4 mg tamsulosin to the patient's complaint with DJ stent based on USSQ parameters. Material & Methods: This was a prospective study conducted in Hasan Sadikin Hospital Bandung from October to December 2017. A total of 60 patients with indwelling DJ stents randomly divided into 2 groups (n=30). The first group was given tamsulosin 0.2mg daily and the second group was given tamsulosin 0.4 mg daily. LUTSs before and after tamsulosin administration for a week were evaluated in both groups using USSQ. Percentage decreases in USSQ score in both groups were then compared using Mann Whitney Test. Results: In group I, USSQ score means were 31.9 (20.0-40.0; SD 31.9) before tamsulosin 0.2 mg administration and 26.1 (15.0-35.0; SD 5.6) after tamsulosin 0.2 mg administration. Comparison test before and after tamsulosin 0.2 mg administration showed significant decrease in USSQ score. In group II, USSQ score means were 38.9 (31.0-44.0; SD 2.9) before tamsulosin 0.4 mg administration and 16.7 (13.0-21.0; SD 1.8) after tamsulosin 0.4 mg administration. Comparison test before and after tamsulosin 0.4 mg administration showed significant decrease in USSQ score. The percentage decreases in USSQ score were 18.7% in group I and 56.9% in group II. Different test score before and after treatment for both groups showed p-value<0.05. Scoring results after treatment showed the effectiveness of tamsulosin 0.4 mg was better than tamsulosin 0.2 mg. Conclusion: LUTS is the most common stent-associated symptom (SAS) in patients with indwelling DJ stent. Independent administration of tamsulosin 0.2 mg and 0.4 mg significantly alleviated SAS. Tamsulosin 0.4 mg had better effectiveness in alleviating SAS compared to tamsulosin 0.2 mg.